An Exceptional Peroxide Birefringent Material Resulting from d–π Interactions. Issue 24 (6th April 2020) - Liu, Shuai; Liu, Xiaomeng; Zhao, Sangen; Liu, Youchao; Li, Lina; Ding, Qingran; Li, Yanqiang; Lin, Zheshuai; Luo, Junhua; Hong, Maochun
Abstract: Birefringent materials, which can modulate the polarization of light, are almost exclusively limited to oxides. Peroxides have long been overlooked as birefringent materials, because they are usually not stable in air. Now, the first peroxide birefringent material Rb2 VO(O2 )2 F is reported, the single crystals of which keep transparency after being exposed in the air for two weeks. Interestingly, Rb2 VO(O2 )2 F does not feature an optimal anisotropic structure, but its birefringence (Δn=0.189 at 546 nm) exceeds those of the majority of oxides. According to the first‐principles calculations, this exceptional birefringence should be attributed to the strong electronic interactions between localized π orbital of O2 2− anions and V 5+ 3d orbitals, which may be also favorable to the stability in the air for Rb2 VO(O2 )2 F. These findings distinguish peroxides as a brand‐new class of birefringent materials that may possess birefringence superior to the traditional oxides. Abstract : Birefringent materials, which can modulate the polarization of light, are almost exclusively limited to oxides. Now, a peroxide birefringent material, Rb2 VO(O2 )2 F, is reported. Single crystals retain transparency after being exposed in the air for two weeks. Rb2 VO(O2 )2 F does not feature an optimal anisotropic structure, but its birefringence (Δ n =0.189 at 546 nm) exceeds those of the majority of oxides.